Counseling to increase public awareness of mangrove forest conservation - Duryat Duryat; Rommy Qurniati; Heryandi Heryandi; Machya Kartika Tsani; Surnayanti Surnayanti; Dadi Anesa (Community Empowerment, 2022)
Margasari village has a mangrove area of ​​approximately 700 ha. As the main actors in mangrove management, the people of Margasari Village need to be equipped with basic knowledge about the role and function of mangroves, mangrove zoning, and types of mangrove vegetation. The purpose of this activity is to increase people's knowledge about mangroves, change people's mindsets towards mangrove conservation, and improve the ability to manage and use mangroves wisely and sustainably. Lectures and discussions as well as demonstrations are used as outreach methods. This activity is able to increase public understanding of the role and function of mangroves, so that it can change the mindset of people who are afraid of the law in maintaining mangroves and they can participate in preserving mangroves. A good understanding of mangrove zoning will change the mindset of the community, which initially considered the most important mangrove plant species to be Rhizophora spp, to all types of mangrove vegetation having an important role in the ecosystem. Increased knowledge about mangrove vegetation types has provided awareness that the Margasari Village area has a very favorable location for various types of mangroves, so that it can be optimized to improve community welfare.